Comparison of perioperative outcomes of robotic vs. laparoscopic partial nephrectomy for renal tumors with a RENAL nephrometry score ≥7: A meta-analysis - Jiang, Yu-Li; Yu, Dong-dong; Xu, Yang; Zhang, Ming-Hua; Peng, Fu-Sheng; Li, Peng (Frontiers in Surgery, 2023)
Abstract Background:To compare the perioperative outcomes of robotic partial nephrectomy (RPN) versus laparoscopic partial nephrectomy (LPN) for complex renal tumors with a RENAL nephrometry score≥7. Methods: We searched PubMed, EMBASE and the Cochrane Central Register for studies from 2000 to 2020 to evaluate the perioperative outcomes of RPN and LPN in patients with a RENAL nephrometry score≥7. We used RevMan 5.2 to pool the data. Results: Seven studies were acquired in our study. No significant differences were found in the estimated blood loss (WMD: 34.49; 95% CI: -75.16-144.14; p=0.54), hospital stay (WMD: -0.59; 95% CI: -1.24–0.06; p=0.07), positive surgical margin (OR: 0.85; 95% CI: 0.65–1.11; p =0.23), major postoperative complications(OR: 0.90; 95% CI: 0.52–1.54; p=0.69) and transfusion (OR: 0.72; 95% CI: 0.48–1.08; p =0.11) between the groups. RPN showed better outcomes in the operating time (WMD: -22.45; 95% CI: -35.06 to -9.85; p=0.0005), postoperative renal function (WMD: 3.32; 95% CI: 0.73–5.91; p=0.01), warm ischemia time (WMD: -6.96; 95% CI: -7.30–-6.62; p <0.0001), conversion rate to radical nephrectomy (OR: 0.34; 95% CI: 0.17 to 0.66; p=0.002) and intraoperative complications (OR: 0.52; 95% CI: 0.28–0.97; p=0.04). Conclusion: RPN is a safe and effective alternative to LPNs for or the treatment of complex renal tumors with a RENAL nephrometry score≥7 with a shorter warm ischemic time and better postoperative renal function.